In situ transport characterization of magnetic states in Nb/Co superconductor/ferromagnet heterostructures - Kapran, Olena M.; Morari, Roman; Golod, Taras; Borodianskyi, Evgenii A.; Boian, Vladimir; Prepelita, Andrei; Klenov, Nikolay; Sidorenko, Anatoli S.; Krasnov, Vladimir M. (Beilstein Journal of Nanotechnology, 2021)
Employment of the non-trivial proximity effect in superconductor/ferromagnet (S/F) heterostructures for the creation of novel superconducting devices requires accurate control of magnetic states in complex thin-film multilayers. In this work, we study experimentally in-plane transport properties of microstructured Nb/Co multilayers. We apply various transport characterization techniques, including magnetoresistance, Hall effect, and the first-order-reversal-curves (FORC) analysis. We demonstrate how FORC can be used for detailed in situ characterization of magnetic states. It reveals that upon reduction of the external field, the magnetization in ferromagnetic layers first rotates in a coherent scissor-like manner, then switches abruptly into the antiparallel state and after that splits into the polydomain state, which gradually turns into the opposite parallel state. The polydomain state is manifested by a profound enhancement of resistance caused by a flux-flow phenomenon, triggered by domain stray fields. The scissor state represents the noncollinear magnetic state in which the unconventional odd-frequency spin-triplet order parameter should appear. The non-hysteretic nature of this state allows for reversible tuning of the magnetic orientation. Thus, we identify the range of parameters and the procedure for in situ control of devices based on S/F heterostructures.
Keywords: cryogenic computing; devices exploiting spin polarized transport or integrated magnetic field; spin-valve; superconducting multilayers; superconducting spintronics